2015
DOI: 10.1177/0961203315605367
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vitamin D, IFN-γ, and E2levels in systemic lupus erythematosus

Abstract: In this study, we investigated the relationship between vitamin D, interferon-gamma (IFN-γ), and estradiol (E2) in females of childbearing age with inactive systemic lupus erythematosus (SLE). The study included 22 SLE patients, and 21 age- and gender-matched healthy individuals. Serum concentrations of 25-hydroxyvitamin D3 (25(OH)D3), E2, and IFN-γ were measured by radioimmunoassay using the gamma-counter and ELISA. Patients and control subjects were divided into two groups based on their vitamin D levels (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
1
20
2
Order By: Relevance
“…However, interventional studies did not reach definite conclusions regarding the clinical efficacy of vitamin D treatment to treat SLE 43 . Our results are in agreement with another study, which showed that the levels of 25(OH)D were negatively associated with IFN‐γ levels 44 . It was demonstrated that 25(OH)D suppresses adaptive immunity, which leads to the inhibition of proliferation and differentiation of CD4 + Th0 cells into Th1 and Th17 cells.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, interventional studies did not reach definite conclusions regarding the clinical efficacy of vitamin D treatment to treat SLE 43 . Our results are in agreement with another study, which showed that the levels of 25(OH)D were negatively associated with IFN‐γ levels 44 . It was demonstrated that 25(OH)D suppresses adaptive immunity, which leads to the inhibition of proliferation and differentiation of CD4 + Th0 cells into Th1 and Th17 cells.…”
Section: Discussionsupporting
confidence: 59%
“…43 Our results are in agreement with another study, which showed that the levels of 25(OH)D were negatively associated with IFN-γ levels. 44 It was demonstrated that 25(OH)D suppresses adaptive immunity, which leads to the inhibition of proliferation and differentiation of CD4 + Th0 cells into Th1 and Th17 cells. 25(OH)D also stimulates Th2 and Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was no difference in IFNγ serum level between CLL and control subjects. Negative correlation between IFN-γ and 25-OH-D 3 was previously reported 44 ; however, we were unable to prove it. In addition, we showed only a tendency toward lowering IFN-γ after VD repletion.…”
Section: Discussioncontrasting
confidence: 55%
“…Our data demonstrated that ex vivo production of IFN-γ is decreased in patients with active disease compared to patients with inactive disease. The results of our study are different from those of previous publications that have reported increased IFN-γ production or IFN-γ-related gene expression in SLE, because our study evaluated IFN-γ production after PHA stimulation in whole blood [ 6 , 7 , 20 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Interferon gamma (IFN-γ) is predominantly produced by T cells and natural killer cells [ 3 ], and it plays a critical role in lupus [ 4 ]. Previous studies have shown that IFN-γ mRNA expression is increased in peripheral blood mononuclear cells (PBMC) [ 5 ], and that serum levels of IFN-γ are elevated in patients with SLE [ 6 , 7 ]. In addition, in vivo experiments in murine models of SLE have shown that elevations in IFN-γ mRNA levels are correlated with disease progression [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%